Synthesis and characterization of iron and copper chalcogenide nanomaterials for photovoltaic applications - Fredrick, Sarah J., author; Prieto, Amy, advisor; Neilson, James, committee member; Rappé, Anthony, committee member; Strauss, Steven, committee member; Williams, John, committee member (Colorado State University. Libraries, 2014)
With our current looming energy and climate crises, it is vital that we find alternative forms of energy that have a lower carbon footprint. Solar technology is an excellent candidate for such purposes as the sun is an essentially unlimited source of renewable energy. However, the cost of solar cells is not economically competitive with fossil fuels. Alternatives to the traditional silicon solar modules could be a path toward reducing the cost of solar technology. The topic of this thesis is the synthesis and characterization of such alternatives. Iron and copper-based materials are earth abundant and potentially more cost-effective. Furthermore, processing these materials as nanocrystals, rather than bulk films, can reduce the energy input for fabricating solar absorber layers, and in turn, reduce overall system costs. Iron pyrite (FeS2) and a related material, Fe2GeS4 are two materials with near ideal properties for solar absorption. While there has been a great deal interest in FeS2, Fe2GeS4 is a novel system on which minimal research has been performed. Herein is described the synthesis and characterization of both of these iron chalcogenides with a particular focus on the challenging surface chemistry presented by these systems. Another system of increasingly widespread interest in recent years in the class of earth-abundant photovoltaic materials is Cu2ZnSnS4 (CZTS). A vast body of literature has been developed, but detailed characterization is lacking in much of the work, hindering our fundamental understanding of the properties. The final chapter of this thesis is a perspective work describing common characterization techniques for CZTS. It analyzes their usefulness in determining the formation of the pure CZTS phase, in hopes of improving current understanding of the material.
Keywords: pyrite; photovoltaics; nanocrystals; CZTS; nanocrystal inks